Cancer Chemotherapy in Early Life Significantly Alters the Maturation of Pain Processing. (1st September 2018) - Hathway, G.J.; Murphy, Emily; Lloyd, Joseph; Greenspon, Charles; Hulse, R.P.
Highlights: Cisplatin exposure early in life causes delayed but long-lasting mechanical and heat hypersensitivity. Cisplatin treatment early in life does not lead to sensory neuron loss in DRG or spinal cord. Early-life exposure to cisplatin leads to increased sensory nerve fiber terminals in the skin and spinal cord. Abstract: Advances in pediatric cancer treatment have led to a ten year survival rate greater than 75%. Platinum-based chemotherapies (e.g. cisplatin) induce peripheral sensory neuropathy in adult and pediatric cancer patients. The period from birth through to adulthood represents a period of maturation within nociceptive systems. Here we investigated how cisplatin impacts upon postnatal maturation of nociceptive systems. Neonatal Wistar rats (Postnatal day (P) 7) were injected (i.p.) daily with either vehicle (PBS) or cisplatin (1mg/kg) for five consecutive days. Neither group developed mechanical or thermal hypersensitivity immediately during or after treatment. At P22 the cisplatin group developed mechanical ( P < 0.05) and thermal ( P < 0.0001) hypersensitivity versus vehicle group. Total DRG or dorsal horn neuronal number did not differ at P45, however there was an increase in intraepidermal nerve fiber density in cisplatin-treated animals at this age. The percentage of IB4 +ve, CGRP+ve and NF200+ve DRG neurons was not different between groups at P45. There was an increase in TrkA+ve DRG neurons in the cisplatin group at P45, in addition to increased TrkA, NF200 and vGLUT2 immunoreactivity in the lumbar dorsal horn versus controls. These data highlight the impact pediatric cancer chemotherapy has upon the maturation of pain pathways and later life pain experience.